REPLACING ORTHOMETRIC HEIGHTS WITH ELLIPSOIDAL HEIGHTS IN ENGINEERING SURVEYS (Nigerian Journal of Technology, 2016)
Differential Global Positioning System (DGPS) is one of the most frequently used positioning methods in geodesy. The end products of surveying with Global Navigation Satellite Systems (GNSS)are geodetic latitude (?), geodetic longitude (?) and ellipsoidal height (h) which are obtained with reference to the ellipsoid.  Recent developments in GNSS technology make us to obtain the ellipsoidal height with high accuracy. In engineering practice, orthometric heights (height above sea level) are always used. The orthometric heights are determined by spirit or geodetic leveling. In transforming the GNSS-derived ellipsoidal heights to orthometric heights, it is important to know the separation between the ellipsoidal and the geoid surface. This work investigates the use of ellipsoidal heights in place of orthometric heights for engineering surveys. DGPS observations were carried out to obtain the ellipsoidal heights for a number of points in the study area in Port Harcourt, Nigeria. Orthometric heights for the same set of points were determined using geodetic levelling. The results satisfied third order levelling which is good enough for engineering surveys. http://dx.doi.org/10.4314/njt.v35i4.10